(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The text refers to the study of the preparation of future teachers at the University, focusing on the cultivation of critical reflection, as a necessary qualification for professional development. Special emphasis is given to practicum in education as part of their education, because in this area the student has the opportunity to be tested, to think and to reflect upon educational practices. This issue emerges from a survey conducted in the context of training preschool teachers in a Greek University. During the investigation, the need to strengthen the reflective skills of future teachers, as well as the potential benefits for their better preparation emerged.